Artificial Intelligence (AI) on Learning Process (International Journal of Integrative Research (IJIR), 2024)
Artificial intelligence (AI) is a helpful technology. Byproviding college students with more individualized andproductive learning environments, they support education.This research examines how artificial intelligence (AI) worksin education and enhances teaching and learning results forMindoro State University students and teachers. The studywill survey students and instructors to gauge theirperspectives on AI, assess its benefits and obstacles ineducation, and propose strategies for successfullyimplementing AI into teaching and learning techniques. Thepoll will ask students about their understanding of AI andtheir experiences using AI-powered learning tools. Accordingto the results of this study, students and teachers at theUniversity have a strong belief and a positive outlook on thepotential of AI to significantly improve the learning journeyand outcomes for both students and instructors, as evidencedby the weighted mean rating of 4.37 for all categoriescombined. Overall, respondents strongly agree that artificialintelligence has the potential to considerably improve studentand instructor learning and teaching outcomes at theUniversity, as indicated by the average mean score of 4.23,which is characterized as "strongly agree." The study'sfindings will provide educators and policymakers withcritical insights into the proper and successful use of artificialintelligence (AI) to improve student learning outcomes
Keywords: Artificial Intelligence, Learning Process, Machine Learning, Revolutionize